In vitro Antifungal efficacy of Saccharomyces Cerevisiae Mediated Nanoparticle Against Resistant Candida Albicans Isolates - Hussein A. R. Abbood1, Bari L.Mohammed2, Hawazin A.Aboid2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dry yeast Saccharomyces. cerevisiae was obtained from markets in Kirkuk and used to study their ability to prepare silver nanoparticles and shows that the silver nitrate solution at 1Mm changes its color to brown and is an initial indication of the formation of nanoparticle particles and X-ray diffraction peaks were measured at (111), (202) and (220) respectively. Particles also appeared in clear minutes in the scanning electron microscopy images at a size of 44 nanometers . A total of 103 vaginal swabs were taken from women who suffered from vaginitis from the Kirkuk General Hospital. The results revealed that Candida types were responsible for 67% of the cases. Candida albicans, C.glabrata, C.tropicalis, C.krusei and C.parapsilosis were isolated. 30.8%, 22.8%, 20%, 15.8% and 11.5%, respectively . In addition, the sensitivity of the drug in the drilling method against the isolates of Candida albicans showed high resistance to fluconazole and gresiofulvin antagonists, with 100% of gresiofulvin (85%) of fluconazole. For nystatin, Resistance ratios (14%) The solution of the nano-silver particles recorded from Saccharomyces Cerevisiae yeast was also shown. had a significant inhibitory effect on Candida albicans, a multi-resistance yeast antimicrobial resistance (21,21,22mm) at 100% and (10,13,10mm)at 50% and inhibition(5, 4,5 mm) has a 35% dilution and a 25% concentration did not receive any inhibition.